Character strengths and virtues in the Greek cultural context - Pezirkianidis, Christos; Karakasidou, Eirini; Stalikas, Anastassios; Moraitou, Despina; Charalambous, Vicky (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The aim of the present study was to examine the conceptual framework of character strengths in the Greek cultural context and, to do so, the factor structure of the Greek version of the Values In Action-120 (VIA-120) inventory of strengths was explored. A lifespan sample of 3,211 Greek adults was used to examine the factorial structure and psychometric characteristics of the measurement. The results indicated that the structure of the 24 character strengths was confirmed and a model of five virtues has emerged. The similarities and differences between the Greek and other cultures’ models are being discussed. The VIA-114GR demonstrated adequate reliability, convergent validity to wellbeing indices, and discriminant validity to negative experiences. Gender and age differences were found in several strengths and virtues. Also, the findings showed that the five signature strengths of the Greek sample were kindness, love, honesty, fairness, and persistence and the five bottom strengths were love of learning, spirituality, perspective, modesty, and self-regulation. Limitations, recommendations for future studies, and practical implications for the use of VIA-114GR are being discussed.